Isolation and Characterization of Acetylcholinesterase Inhibitors from Piper longum and Binding Mode Predictions - Khatami, Zakie; Herdlinger, Sonja; Sarkhail, Parisa; Zehl, Martin; Kaehlig, Hanspeter; Schuster, Daniela; Adhami, Hamid-Reza (Planta Medica, 2020)
Restoration of cholinergic function is considered a rational approach to enhance cognitive performance. Acetylcholinesterase inhibitors are still the best therapeutic option for Alzheimerʼs disease. The fruits of Piper longum have been used in traditional medicines for the treatment of memory loss. It was demonstrated that the dichloromethane extract of these fruits is able to inhibit acetylcholinesterase. Thus, the aim of this study was to identify the contained acetylcholinesterase inhibitors. The active zones were presented via TLC-bioautography, and five compounds were isolated in the process of a bioassay-guided phytochemical investigation. Their structures were characterized as piperine, methyl piperate, guineenisine, pipercide, and pellitorine using spectroscopy and spectrometry methods (UV, IR, MS, 1H-, and 13C-NMR). In vitro acetylcholinesterase inhibitory activities of the isolates and their IC50 values were determined via a colorimetric assay. Three of them exhibited enzyme inhibitory activities, with piperine being the most potent compound (IC50 of 0.3 mM). In order to investigate the binding mode of the tested compounds, docking studies were performed using the X-ray crystal structure of acetylcholinesterase from Tetronarce californica with the Protein Data Bank code 1EVE. The content of the active compounds in the extract was determined by a developed HPLC method. Piperine was present in the maximum quantity in the fruits (0.57%), whereas methyl piperate contained the minimum content (0.10%).
Keywords: Alzheimerʼs disease; AChE inhibitor; Piper longum; Piperaceae; piperine; pipercide; guineensine